Is age an independent risk factor for medical complications following minimally invasive radical prostatectomy? An evaluation of contemporary American College of Surgeons National Surgical Quality Improvement (ACS-NSQIP) data. Issue 4 (December 2016) - Dagrosa, Lawrence; Ingimarsson, Johann; Gorlov, Ivan; Higgins, John; Hyams, Elias
Abstract While robotic-assisted laparoscopic radical prostatectomy (RALRP) is an effective treatment for localized prostate cancer, the risk of complications in older patients can be a deterrent to surgery. We evaluated the rate of medical complications following RALRP in a national dataset of safety events, and assessed whether age is an independent risk factor for these complications. Retrospective analysis of patients undergoing RALRP between 2009 and 2012 in the prospectively maintained American College of Surgeons National Surgical Quality Improvement (ACS-NSQIP) database was performed. Demographic and comorbid data were collated, medical complications occurring during the 30-day post-operative period were identified. We identified age-related comorbidities, and complications associated with these comorbidities. A binary logistic regression model with age and age-related comorbidities as predictors and specific complication as outcome, was used to evaluate whether age is an independent risk factor for these complications. 12, 123 patients underwent RALRP between 2009 and 2012, with a mean age of 62 (22–92). Post-operative medical complications included urinary tract infection (UTI) (1.77 %), deep venous thrombosis (DVT) (0.67 %), pulmonary embolism (PE) (0.45 %), pneumonia (PNA) (0.27 %), myocardial infarction (MI) (0.12 %), and cerebrovascular accident (CVA) (0.01 %). Nine comorbidities were positively correlated with age (p  < 0.05). Four medical complications were associated with these age-related comorbidities: MI, CVA, PNA, and UTI. On multivariate analysis, age was an independent risk factor for post-operative PNA (p  < 0.05), but not for MI (p  = 0.09), UTI (p  = 0.3) or CVA (p  = 0.2). Patient age was independently associated with post-operative pneumonia only. These data suggest that RALRP can be considered as a treatment option in selected older patients with minimal increased risk for post-operative complications.